The influence of school culture and self-esteem on the character of early childhood teachers - Robingatin, Robingatin; Komariah, Anis (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to determine how much influence Early Childhood teachers’ self-esteem on character, the influence of school culture on the character of Early Childhood Teachers, and the influence of self-esteem and school culture on the character of Early Childhood Teachers. To obtain the data using a questionnaire. The type of research is a quantitative explanatory approach. Data analysis was performed by multiple regression analysis. The results of data analysis show the Pearson correlation value of self-esteem (X1) with the character of early childhood teachers (Y) of 0.576. It shows that the strength of the relationship between self-esteem (X1) and the character of early childhood teachers (Y) is in the moderate category. Furthermore, the Pearson correlation value of school culture (X2) with the character of early childhood teachers (Y) is 0.793. It shows that the strength of the relationship between school culture (X2) and the character of early childhood teachers (Y) is included in the strong category. The double correlation of X1 and X2 with Y is significant. It means there is an effect of self-esteem and school culture on the character of early childhood teachers. Furthermore, the Pearson correlation value is 0.828. It shows that the strength of the relationship between self-esteem (X1) and school culture (X2) with the character of early childhood teachers (Y) is included in the very strong category. The product-moment correlation between X1 and X2 with Y (Ryx1x2) is 0.828. It means that self-esteem and school culture affect the personality of Early Childhood Teachers, which is the research's novelty.